Income inequality, consumption, and the debt ratio of Chinese households - Zhaolin Shen; Wei Fan; Jiang Hu (PLoS ONE, 2022)
The increasing family leverage and the expansion of income inequality have aroused widespread concern in society. Based on the data from the China Household Finance Survey (CFPS), this paper constructs the Gini coefficient and household credit index, and aims to research the impact of income inequality, borrowing level on consumption in different regions, urban and rural areas. The results indicate that the increasing of income inequality significantly restrained the increase of household consumption, while the moderate increase of household leverage can promote household consumption to a certain extent. According to the conclusion of this article, in order to realize the sustainable growth of consumption and upgrade of structure, the government should take measures to stimulate domestic demand: (1) For the central and western regions, the overall wealth level of households should be improved and the borrowing level of residents should be appropriately increased; (2) For the eastern region, the income inequality should be controlled and reduced the negative effects of income inequality on sustainable consumption growth. This research provides evidence for understanding the relationship between income inequality, household leverage ratio and consumption, and sheds light on the formulation of related policies.